Disentangling the Subalpine Marshmarigold Species Complex: the Cytogeography, Phylogeography, and Systematics of Caltha Biflora DC., C. Chionophila Greene, and C. Leptosepala DC. (Ranunculaceae) - (:unkn) unknown (My University, 2018)
Subalpine marshmarigolds (Caltha biflora DC., C. chionophila DC., and C. leptosepala Greene, Ranunculaceae) are herbaceous perennials that grow in western North American mountainous and subarctic regions, from Alaska and Yukon in the north to California, Arizona, and New Mexico in the south. Variation in morphology across the range has generally led to recognition of a single species, though some have described up to nine species in the complex. In this dissertation, I describe our approaches to disentangling reticulate evolution across the geographical range of the subalpine marshmarigold complex, including chromosome counts (Chapter II), genome size estimates (Chapter III), morphology (Chapters III and IV), taxonomic circumscription (Chapter IV), and a dated phylogeographic reconstruction of divergence, migration, and allopolyploidization (Chapter V). This work delineates three species in the complex, including two hexaploid species (C. biflora in the Cascades, Sierra Nevada, and Coastal Ranges, and C. chionophila in the Rockies), a rare allononaploid (C. leptosepala in a single population in the Northern Rockies), and a widespread allododecaploid (C. leptosepala more or less throughout the range excluding the southern Rockies). The hexaploids are estimated to have diverged in the Upper Miocene to Upper Pliocene, persisted to the south (and possibly west) of Last Glacial Maximum icesheets, formed allododecaploids multiple times in the late Cenozoic, and recolonized deglaciated regions in multiple waves during the Pleistocene.
Keywords: allopolyploid; Cenozoic; hybrid; Pacific Northwest; refugia; speciation